2011
DOI: 10.1128/aac.00215-10
|View full text |Cite
|
Sign up to set email alerts
|

Development of Tetravalent, Bispecific CCR5 Antibodies with Antiviral Activity against CCR5 Monoclonal Antibody-Resistant HIV-1 Strains

Abstract: In this study, we describe novel tetravalent, bispecific antibody derivatives that bind two different epitopes on the HIV coreceptor CCR5. The basic protein formats that we applied were derived from Morrison-type bispecific antibodies: whole IgGs to which we connected single-chain antibodies (scFvs) via (Gly 4 Ser) n sequences at either the C or N terminus of the light chain or heavy chain. By design optimization, including disulfide stabilization of scFvs or introduction of 30-amino-acid linkers, stable molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…Continuing efforts will be given to address this issue in future studies. Schanzer et al (48) recently demonstrated that a bi-specific CCR5 antibody displays potent neutralizing activity against resistant viruses by targeting both the Nt and ECL2. Our future studies should investigate the potency of TD-0680 on other R5-tropic non-competitive CCR5 antagonist-resistant viruses, which might be more dependent on the Nt of CCR5 for entry (41,45).…”
Section: Discussionmentioning
confidence: 99%
“…Continuing efforts will be given to address this issue in future studies. Schanzer et al (48) recently demonstrated that a bi-specific CCR5 antibody displays potent neutralizing activity against resistant viruses by targeting both the Nt and ECL2. Our future studies should investigate the potency of TD-0680 on other R5-tropic non-competitive CCR5 antagonist-resistant viruses, which might be more dependent on the Nt of CCR5 for entry (41,45).…”
Section: Discussionmentioning
confidence: 99%
“…ScFv molecules have been fused to the N-terminus but also the C-terminus of the of the heavy or light chain of a mAb, [21][22][23] generally without compromising productivity or antigen-binding activity, although issues regarding stability have recently been addressed. 24 This group of IgG-like bispecific molecules also includes DVD-Igs, where a second V H and V L domain is fused to the heavy and light chain, respectively, of a mAb, 25 two-in-one antibodies, where a second specificity is introduced into the natural binding site of an IgG molecule, 26 and mAb 2 molecules, where a second specificity is build into the C H 3 domain of the Fc region. 27 A characteristic feature of all these molecules is a symmetry caused by dimeric assembly of two identical heavy chains, an intrinsic property of these chains.…”
Section: Dual Targeting Strategiesmentioning
confidence: 99%
“…21,22,31 Previous studies have found that inclusion of a number of design modifications, including variations in CH3-scFv linker length and type, and also scFv stability engineering via addition of disulfide bonds, improved construct stability. [70][71][72][73][74][75] A concern with the Fc-linked dimeric design was whether the presence of 2 anti-LPS scFvs would result in EDV TM nanocell aggregation via binding of multiple nanocells rather than high avidity binding of a single nanocell. An alternative Fc-linked BsAb was engineered consisting of 2 EGFR targeting scFvs at the N-terminus (high avidity) and a single anti-LPS scFv at the C-terminus of the final product.…”
Section: Wwwtandfonlinecom 59 Mabsmentioning
confidence: 99%
“…Cysteine stabilization substitutions were made at Kabat position VH44 and VL100 of the scFvs. 72,73 Variants included either a short (G4S) linker or a longer linker (SSDKTHTSPPSPGGGGSGGGGSGGGGSGGGG), as described in Moore et al, connecting the CH3 domain to the 1H10-scFv. 75 A "knob" was produced by amino acid substitution for a longer side chain (T366'W), whereas a "hole" was produced by amino acid substitutions for shorter side chains (T366'S:L368'A:Y407'V); the sequence positions are as indicated by Kabat et al 80 The tandem scFv included 6xHis and c-myc tags for purification and detection, while the other constructs utilised the Fc domain for purification and detection.…”
Section: Sequence Designmentioning
confidence: 99%